EC Competition Law and Policy. - Albors-Llorens, Albertina (Willan Pub., 2002)
This book provides a clear overview of the main issues in EC competition law and policy and an up to date text for students and practitioners with an interest in this subject. It is divided into three main parts, looking at the foundations of EC competition law, anti-competition agreements, abuse of dominant position, and the enforcement of EC competition law. The book focuses on the two main Treaty Articles which are concerned with competition law. It aims to provide a structured analysis of the main stages in the application of the EC Treaty rules on competition, assesses the contribution ma.